Progressive Outcomes: is it a handy approach to support agile methods process improvement? - Fontana, Rafaela Mantovani; Reinehr, Sheila; Malucelli, Andreia (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2015: Anais do XIV Simpósio Brasileiro de Qualidade de Software, 2015)
While software engineering relies on reference models, such as CMMI-DEV, to improve its processes and gain maturity; agile teams that wish to sustain agility demand other guidelines to drive improvements. To address this need, in a previous study we have proposed the Progressive Outcomes Framework as a result of a research about how real agile teams evolve in agility. Although we could describe agile maturing mechanisms, we lacked a perception of how handy out approach would be to guide improvements. The objective of this study was, thus, to identify agile practitioners’ perception about the framework. We performed a survey with agile practitioners in Brazilian conferences and analyzed collected data using descriptive statistics. Results show that agile practitioners feel comfortable in following non- prescriptive guidelines, but they still lack guidance on how to improve in agility.